2002
DOI: 10.1046/j.1365-2427.2002.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modelling of freshwater fish as a biomonitoring tool in New Zealand

Abstract: SUMMARY 1. A challenge has been issued to ecologists to find quantitative ecological relationships that have predictive power. A predictive approach has been successful when applied to biomonitoring using stream invertebrates with the River Invertebrate Prediction and Classification System (RIVPACS). This approach, to our knowledge, has not been applied to freshwater fish assemblages. 2. This paper describes the initial results of the application of a regional predictive model of freshwater fish occurrence usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 43 publications
4
72
0
2
Order By: Relevance
“…This highlights the need to consider the use of different life stages when making spatial distribution assessments that are particularly important from a conservation point of view. Though the large-scale gradient of longitudinal position has been shown to influence fish distribution within river systems elsewhere (Joy and Death 2002;Mugodo et al 2006), other factors were also important in shaping the spatial organisation of species life stages.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need to consider the use of different life stages when making spatial distribution assessments that are particularly important from a conservation point of view. Though the large-scale gradient of longitudinal position has been shown to influence fish distribution within river systems elsewhere (Joy and Death 2002;Mugodo et al 2006), other factors were also important in shaping the spatial organisation of species life stages.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs because reservoirs reduce the natural amplitude of water levels variation, consequently changing the dynamics of aquatic communities (Ward & Stanford 1995). The resulting ecological damage may have economic and social impacts in human communities, since recent studies indicated that biodiversity ensures the maintenance of ecosystem processes, buffering the effects of detrimental changes (Galat & Lipkin 2000, Joy & Death 2002, Naeem 2002, Srivastava & Vellend 2005). …”
mentioning
confidence: 99%
“…Oberdorff et al, 2001) as well as neural networks (e.g. Boet and Fuhs, 2000;Joy and Death, 2002;Mastrorillo et al, 1997;Olden and Jackson, 2001;Scardi et al, 2004Scardi et al, , 2005. The expert system we developed, however, goes a step farther, because it leverages an Artificial Intelligence approach in the strictest sense, i.e.…”
Section: Discussionmentioning
confidence: 99%